Dichotomija (simmetrija-asimmetrija) fiziceskogo razvitija sportsmenov - Kozlov, I. M.; Samsonova, A. V.; Stepanov, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research was to study the dichotomy of physical development of athletes in three-dimensional space: the morphological parameters concerning sagittal, frontal and transverse planes were determined. Weight-lifters of high qualification and the athletes with a sports rating participated in the experiments.